2004
DOI: 10.1002/adem.200300542
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Refractive Index of Polymers for Polymer Waveguides Using Nanoscaled Ceramics or Organic Dyes

Abstract: Plastic Optical Fibers (POF) show advantageous properties like high flexibility and their cost advantage in comparison to glass fibers. The refractive indices of core and cladding have to be modified in order to get total reflectance. Thus, there is a strong demand for refractive index adjustable polymers with improved transmission properties in the visible and the NIR range. Inorganic nanosized particles or organic dyes homogeniously dispersed or solved in the polymer matrix allow a tailored increase or decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 7 publications
2
35
0
1
Order By: Relevance
“…[18][19][20] The scattering and the resulting optical damping in the polymer-nanofiller-composites depend strongly on the applied dispersion method, due to the different deagglomeration forces of the used techniques. [18] Surface-modified silica nanoparticles can be filled in acrylate-based resins to a larger load up to 50 wt.-%; in combination with the acrylate composition using bisphenol-A-diacrylate as a co-monomer, a refractive index tuning between 1.48 and 1.51 at 633 nm is possible.…”
Section: Full Papermentioning
confidence: 99%
See 2 more Smart Citations
“…[18][19][20] The scattering and the resulting optical damping in the polymer-nanofiller-composites depend strongly on the applied dispersion method, due to the different deagglomeration forces of the used techniques. [18] Surface-modified silica nanoparticles can be filled in acrylate-based resins to a larger load up to 50 wt.-%; in combination with the acrylate composition using bisphenol-A-diacrylate as a co-monomer, a refractive index tuning between 1.48 and 1.51 at 633 nm is possible.…”
Section: Full Papermentioning
confidence: 99%
“…[18][19][20] The scattering and the resulting optical damping in the polymer-nanofiller-composites depend strongly on the applied dispersion method, due to the different deagglomeration forces of the used techniques. [18] Surface-modified silica nanoparticles can be filled in acrylate-based resins to a larger load up to 50 wt.-%; in combination with the acrylate composition using bisphenol-A-diacrylate as a co-monomer, a refractive index tuning between 1.48 and 1.51 at 633 nm is possible. [21] The addition of small, electron-rich, organic dopants to polymers is often motivated by the dopant's fluorescence behaviour detecting high-energy radiation or polymermatrix phase transitions, [22] the realisation of waveguides with particular, non-linear optical properties, [23] or the refractive-index modification of methacrylates in the NIR-range.…”
Section: Full Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its optical clarity and known chemical and physical properties, poly(methyl methacrylate) (PMMA, Plexiglas) is an excellent host for functional particles. Various types of metal oxide fillers such as Bi 4 10 Lee and Chen 7 described the preparation of highrefractive-index hybrid films using trialkoxysilane-capped TiO 2 particles. The authors reported a linear increase of the refractive index with TiO 2 content.…”
Section: Introductionmentioning
confidence: 99%
“…This can be done by the addition of nanoparticles with various refractive indices to the polymer. Bohm 79 , et al reported additions of nanoparticle zirconia, alumina, and silica to poly (methyl methacrylate) and they were able to adjust the refractive index over a sufficient range. Levels up to 10 Wt % loading were reported.…”
Section: Refractive Index Tuningmentioning
confidence: 99%